انتاجیة المرأة العربیة فى مجال العلوم والتکنولوجیا کمخرجات بحثیة فى قواعد البیانات العالمیة : دراسة سیانتومتریة - د. متولى على الدکر (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims at identifying the contributions of Arab women in the fieldof science and technology at the international level to provide a general picture ofthe participation of Arab women in world scientific production in this field. Thepaper highlights the role of women in science and the gap in researchproductivity between men and women. Highlighting policy decisions to promotewomen's research in Arab countries. The list of research papers published byArab researchers in the field of science and technology was obtained from the ISIWeb of Science database from 1979 to 2017. Based on the Scientometricsmethod The analysis revealed that researches of Arab women in science andtechnology, 29.2% of the total published in science and technology, Prepared by498 women. The field of education and educational research ranked first inresearch disciplines related to science and technology, And Saudi women rankedfirst in terms of the total number of Arab women's research with 75 researches by20.2%. International cooperation contributed to the publication of a large numberof Arab women's research published internationally in the field of science andtechnology. The researcher Najla Sami Abdul Aziz, For the interior design, AjmanUniversity of Science and Technology of the UAE has the highest productivitywith 6 researches, and the superiority of co-authorship on individual authorship,where the number of joint researches in which more than 303 researchers andresearchers contributed 83.1% of the total research of Arab women